THE EPIDEMIOLOGICAL AND CLINICOPSYCHOLOGICAL CHARACTERISTICS OF HEADACHE IN PARTICIPANTS OF LOCALMILITARY CONFLICTS - E. V. Mikhaylova; K. A. Yakunin; A. P. Rachin (Неврология, нейропсихиатрия, психосоматика, 2009)
Headache is an urgent problem of modern medicine. The purpose of the investigation was to study the pattern and clinicopsychological aspects of headache in participants of local military conflicts (LMC). Among the examined participants of LMC (n = 162), 69.8% complained of headache. The clinicopsychological characteristics of posttraumatic and exertion-induced headache are presented depending on the type of LMC.